FIRST RESULTS OF THE NEW HUNGARIAN HYPERTENSION REGISTRY: NUMBER OF DAILY MEASUREMENTS AND PROPORTION OF PATIENTS IN DIFFERENT BLOOD PRESSURE CATEGORIES. (April 2021) - Nemcsik, János; Habony, Norbert; Ábrahám, György; Farsang, Csaba; Simon, Attila; Benczúr, Béla; Páll, Dénes; Járai, Zoltán
Abstract : Objective: Hypertension is a major public health problem and its proper diagnosis and treatment are crucial points of cardiovascular morbidity and mortality reduction. The aim of the new Hungarian Hypertension Registry is to evaluate the features of blood pressure measurement practice of family physicians and hypertension care specialists and to overview the blood pressure values measured during everyday practice. Design and method: Omron M3 IT devices are located for four months periods in repeated times between October 2018 and October 2023 to family physician practices and to hypertension outpatient clinics. Blood pressure values are transmitted online to an evaluating center using the Medistance system of Omron. Results: Until now 1, 691 family physicians, 111 internists, 112 cardiologists and 12 hypertension specialists were being involved into the study. During 4 four-months long evaluation periods between October 2018 and October 2020, 1 701 927 blood pressure measurements were registered. The daily average number of the measurements in the three periods were 3.5, 4.8, 5.4 and 3.6, respectively. Following the ESH diagnostic criteria, the proportion of subjects in optimal, normal and high-normal blood pressure categories were 13.4%, 13.4% and 17%, respectively. The proportion of patients in stage 1, stage 2 and stage 3 hypertension categories were 32.1%, 17% and 7.1%, respectively. The average systolic blood pressure values in family physician practices with more than 2500 patients were higher compared with practices with less, than 1500 patients (141.8 mmHg versus 139.84 mmHg, respectively). Conclusions: In conclusions, the low daily average number of blood pressure measurements refers for limited blood pressure screening capacity of the Hungarian family physicians. In practices with more patients the blood pressure is generally less controlled. These results suggest the need for reconsideration of the blood pressure measurement guidelines and the further promotion of home blood pressure measurement.